The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ani9060374
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Regulation of Intracellular Signaling Pathways and Target Gene Expression in Bovine Ovarian Granulosa Cells

Abstract: In the present study, AA was used to challenge bovine ovarian granulosa cells in vitro and the related parameters of cellular and molecular biology were measured. The results indicated that lower doses of AA increased survival of bovine granulosa cells whereas higher doses of AA suppressed survival. While lower doses of AA induced accumulation of lipid droplet in granulosa cells, the higher dose of AA inhibited lipid accumulation, and AA increased abundance of FABP3, CD36 and SLC27A1 mRNA. Higher doses of AA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results indicate that OA and LA may induce premature luteinization of GCs. Zhang et al 2019 [62] recently reported effects of AA on bovine GCs. It is clear from their data that AA induces ERK and Akt phosphorylation similar to OA and LA.…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
“…The result was different from that of P4 production that decreased after 2-day exposure to α-zearalenol in bovine large follicle granulose cells [16]. The apoptosis of GCs could partly explain the reason for the decrease of E 2 secretion [36]. In addition, the change in HSP expression induced by stress could control hormonal functions [37].…”
Section: Discussionmentioning
confidence: 80%